Respuestas
Respuesta dada por:
0
1).
![1) \: (1.1) \: a \: las \: 3 \: para \: sacar \: la \: (n) \\ es \\ \: y = mx + n \\ 1 = 3(1) + n \\ 1 = 3 + n \\ - n = 3 - 1 \\ - n = 2 \\ \\ n = - 2 y \: asi \: es \: \\ 2) \: (2.3)a \: las2 \\ y = mx + n \\ 3 = 2(2) + n \\ 3 = 4 + n \\ - n = 4 - 3 \\ - n = 1 \\ n = - 1 1) \: (1.1) \: a \: las \: 3 \: para \: sacar \: la \: (n) \\ es \\ \: y = mx + n \\ 1 = 3(1) + n \\ 1 = 3 + n \\ - n = 3 - 1 \\ - n = 2 \\ \\ n = - 2 y \: asi \: es \: \\ 2) \: (2.3)a \: las2 \\ y = mx + n \\ 3 = 2(2) + n \\ 3 = 4 + n \\ - n = 4 - 3 \\ - n = 1 \\ n = - 1](https://tex.z-dn.net/?f=1%29+%5C%3A+%281.1%29+%5C%3A+a+%5C%3A+las+%5C%3A+3+%5C%3A+para+%5C%3A+sacar+%5C%3A+la+%5C%3A+%28n%29+%5C%5C+es+%5C%5C++%5C%3A+y+%3D+mx+%2B+n+%5C%5C+1+%3D+3%281%29+%2B+n+%5C%5C+1+%3D+3+%2B+n+%5C%5C++-+n+%3D+3+-+1+%5C%5C++-+n+%3D+2+%5C%5C+%5C%5C+n+%3D++-+2+y+%5C%3A+asi+%5C%3A+es+%5C%3A++%5C%5C+2%29+%5C%3A+%282.3%29a+%5C%3A+las2+%5C%5C+y+%3D+mx+%2B+n+%5C%5C+3+%3D+2%282%29+++%2B+n+%5C%5C+3+%3D+4+%2B+n+%5C%5C++-+n+%3D+4+-+3+%5C%5C+-++n+%3D+1+%5C%5C+n+%3D++-+1)
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años